The Influence of Adhocracy Culture on Teacher Performance in Realizing the Transformation of Islamic Education in Madrasah - Lestari, Sri (JURNAL AL-TANZIM, 2025)
21st-century education demands a transformation of Islamic education that is adaptive, innovative, and relevant to current developments. However, teacher performance in Islamic Senior High Schools (Madrasah Aliyah) remains suboptimal due to a limited supportive organizational culture. This study aims to analyze the influence of adhocracy culture, which encompasses innovation, creativity, flexibility, and risk-taking, on teacher performance in realizing the transformation of Islamic education. This study employed a quantitative method with a causal-associative approach. The sample consisted of 36 Madrasah Aliyah teachers, with instruments that had been tested for validity and reliability. Data were analyzed using simple linear regression. The results showed that adhocracy culture had a positive and significant effect on teacher performance, with an R² value of 0.520, a regression coefficient of 0.615, and a p-value of 0.000 (<0.05). This means that 52% of teacher performance is influenced by adhocracy culture. The implications of this study highlight the importance of strengthening adhocracy culture in madrasas to create an organizational climate that fosters innovation, professionalism, and teacher collaboration, thereby enabling the progressive transformation of Islamic education and its global competitiveness.